2015
DOI: 10.3390/rs70302692
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Airborne LiDAR and Satellite Hyperspectral Remote Sensing to Estimate Vascular Plant Richness in Deciduous Mediterranean Forests of Central Chile

Abstract: Abstract:The Andes foothills of central Chile are characterized by high levels of floristic diversity in a scenario, which offers little protection by public protected areas. Knowledge of the spatial distribution of this diversity must be gained in order to aid in conservation management. Heterogeneous environmental conditions involve an important number of niches closely related to species richness. Remote sensing information derived from satellite hyperspectral and airborne Light Detection and Ranging (LiDAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 105 publications
(165 reference statements)
0
22
0
1
Order By: Relevance
“…, Ceballos et al. ). Therefore, we incite researchers to carefully design studies giving insight into how LIDAR and spectral remote sensing can be amalgamated to effectively complement each other and consequently improve the prediction of local biodiversity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, Ceballos et al. ). Therefore, we incite researchers to carefully design studies giving insight into how LIDAR and spectral remote sensing can be amalgamated to effectively complement each other and consequently improve the prediction of local biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…Light Detection and Ranging is increasingly used as a tool for exploring, explaining, and predicting biodiversity (Ceballos et al. , Peura et al. , Zellweger et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research scientists and other subject matter experts submitted innovative and challenging papers that showed advances in several topics: estimating the spatial distribution of plant species richness by Light Detection and Ranging (LiDAR) and hyperspectral data [1], assessing habitat quality of forest corridor based on NDVI [2], applying remote sensing to study (marine) coral ecosystems [3], identifying ecosystem functional types [4], distinguishing between different forest trunk size classes from remote sensing [5], detecting changes in forest patterns [6], applying light use efficiency models to estimate vegetation productivity [7], classifying grassland successional stages by airborne hyperspectral images [8], proposing monitoring programs of grasslands based on multi-temporal optical and radar satellite images [9], estimating the potential of remote sensing to capture field-based plants phenology [10].…”
Section: The Value Of the Special Issuementioning
confidence: 99%
“…Several studies revealed that forest application results from satellite hyperspectral data had a good match with results from airborne hyperspectral data (Townsend & Foster, 2002;Smith 2003). However, some authors stressed that hyperspectral satellite data demonstrated poor performance related to airborne data in such tasks as forest species mapping and canopy water content (Ustin et al, 2002;Ceballos et al, 2015).…”
Section: Introductionmentioning
confidence: 99%